2011
DOI: 10.1002/hed.21777
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable analysis of risk factors for enlargement of the tracheoesophageal puncture after total laryngectomy

Abstract: Background Enlarged tracheoesophageal puncture (TEP) is a challenging complication of surgical prosthetic voice restoration. Prevention of this complication requires identification of high risk individuals, as well as surgical and prosthetic correlates of TEP enlargement. Methods Multivariable logistic regression methods were used to analyze preoperative, perioperative, and postoperative risk factors for enlarged TEP in a 5-year retrospective cohort. Results Enlarged TEP only occurred in irradiated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 25 publications
2
69
0
4
Order By: Relevance
“…Consistent with previously published results, 4 patients with N + primary disease were 6.6-fold more likely to develop an enlarged TEP than patients with N0 primary disease. However, neck dissections, which are more commonly performed in patients with node-positive disease, did not significantly increase the risk of an enlarged TEP.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previously published results, 4 patients with N + primary disease were 6.6-fold more likely to develop an enlarged TEP than patients with N0 primary disease. However, neck dissections, which are more commonly performed in patients with node-positive disease, did not significantly increase the risk of an enlarged TEP.…”
Section: Resultssupporting
confidence: 92%
“…A detailed description of this cohort has been previously published. 4 A summary of patient characteristics is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salvage TL was required for radionecrosis or intractable aspiration in only 1.4% of patients (7/517) randomized to laryngeal preservation regimens for advanced stage squamous carcinoma in the Radiation Therapy Oncology Group 91-11 trial, 8 and accounted for only 3% to 8% of laryngectomies reported in two published cohort studies. 9,10 A review of the literature yields no summary of outcomes after elective TL for dysfunction in disease-free HNC survivors, but there is evidence from a single case-study that swallowing physiology remains impaired despite the fact that aspiration is controlled after TL. 4 The intent of the current study was not to confirm the known fact that TL relieves intractable aspiration.…”
Section: Introductionmentioning
confidence: 99%